A Comparative Study on a Cationic Dye Removal through Homogeneous and Heterogeneous Fenton Oxidation Systems - Pouran, Shima Rahim; Bayrami, Abolfazl; Shafeeyan, Mohammad Saleh; Abdul Raman, Abdul Aziz; Daud, Wan Mohd Ashri Wan (Slovenian Chemical Society, 2018)
Oxidative treatment of a cationic dye solution, methylene blue, was investigated using magnetite nanoparticles and goethite in heterogeneous Fenton-like reaction, and ferrous ions in homogeneous Fenton-reaction. The aim was to compare the degradation efficiencies of the studied catalysts for decolorization of methylene blue solution as the model organic pollutant. Response surface methodology (RSM) was applied to determine the optimal operational conditions for magnetite/H2O2 and goethite/H2O2 systems. The [H2O2] of 0.2 M, catalyst dosage of 1 g/L, pH 9.0 and reaction time of 5h were chosen by RSM. The pH value of 3.0 was used in the case of Fe+2/H2O2 system. The experimental results showed that homogeneous Fenton oxidation system was the most effective system under both acidic and neutral conditions but decreased at pH value of 9.0 due to the decrease in available Fe2+ ions in the solution and generation of ferric hydroxide sludge. Fe3O4/H2O2 system represented better removal efficiency than FeO(OH)/H2O2 system that could be attributed to the presence of FeII cations in magnetite structure and its larger surface area.